Connectivity to Prosperity: ICT Adoption Strategies for Asian LDCs - Thapa, Deepak (SADGAMAYA, 2025)
This paper explores the link between ICT adoption and socioeconomic challenges in the least developed countries. It highlights the role of ICT components, such as mobile network coverage, internet connectivity, and social media, in addressing poverty, unemployment, and slow economic growth. However, a lack of investment, poor infrastructure, and flawed government policies hinder the adoption of ICT, resulting in a 'Technology Gap' that hinders socioeconomic reform. Prioritizing ICT adoption can reduce poverty and unemployment and increase economic growth.